2017
DOI: 10.1007/s10620-017-4817-2
|View full text |Cite
|
Sign up to set email alerts
|

Food-Induced Acute Pancreatitis

Abstract: Food allergy, a commonly increasing problem worldwide, defined as an adverse immune response to food. A variety of immune-related effector cells such as mast cells, eosinophils, neutrophils, and T cells are involved in food-related allergic responses categorized as IgE-mediated, non-IgE mediated, and mixed (IgE and non-IgE) depending upon underlying immunological mechanisms. The dietary antigens mainly target the gastrointestinal tract including pancreas that gets inflamed due to food allergy and leads acute p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 73 publications
(122 reference statements)
0
17
0
Order By: Relevance
“…Acute pancreatitis in patients with immediate FA, however, has occasionally been reported. 8,9 This study has shown that pancreatic dysfunction is not a rare complication of immediate FA because an increase in serum amylase was observed in one-third of OFC-positive patients after OFC.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Acute pancreatitis in patients with immediate FA, however, has occasionally been reported. 8,9 This study has shown that pancreatic dysfunction is not a rare complication of immediate FA because an increase in serum amylase was observed in one-third of OFC-positive patients after OFC.…”
Section: Discussionmentioning
confidence: 84%
“…Acute pancreatitis due to immediate FA has been sporadically reported . In some cases, pancreatitis developed after oral food challenge (OFC) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pancreatitis is a disease defined as an acute or chronic inflammatory process of the pancreas and characterised by the induced pro-inflammatory cytokines, chemokines and tissue recruitment of inflammatory cells, including monocytes, macrophages, and eosinophils [1][2][3][4][5]. Eosinophils are immune cells, and they play a key role in the mucosal immune system of the gastrointestinal tract during normal and inflammatory conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of many hypotheses of the development of acute pancreatitis such as duct hypertension, pancreatic reflux, vascular, allergic, neuro-reflex, infectious, journal homepage: https://morphology-journal.com Vol. 24, №1, Page 34-38 negative consequences [13,14,15,16,17,18].…”
Section: Introductionmentioning
confidence: 99%